Reconceptualizing tourism promotion: the impact of drone photography on marketing tuba island through Szarkowski's theoretical framework - Azman, Mohammad Firdaus; Padil, Md Nagib; Sulaiman, Shahrunizam (Faculty of Art and Design, 2025)
This research initiative intends to evaluate how drone photography might help the visual marketing of Tuba Island. Using Szarkowski's theoretical framework, this study explores the comparative strengths of conventional eye-level photography and modern drone photographs in boosting the island's appeal on tourism websites. The results reveal that drone photography is a more successful instrument for tourism promotion, delivering novel perspectives that greatly boost the visually appeal and emotional impact of Tuba Island. The visual comparative analysis and the poll results demonstrate a strong preference for aerial (drone) imagery over standard eye level photography when advertising Tuba Island as a tourist attraction. Overall, this research demonstrates that drone imagery is regarded to be a very useful tool for tourist promotion, enabling unique techniques to promote island areas such as Tuba Island. These findings underscore the necessity of introducing drone photography into tourism marketing activities to create more beautiful and engaging visual portrayal of destinations.